Real interest rate and house prices in Malaysia: An empirical study - Tang, Tuck Cheong; Tan, Pei Pei (Economics Bulletin, 2015)
This study examines the relationship between real interest rate and real house prices in Malaysia. The analysis covers recent quarterly data from 2001 to 2013. The regression results show a negative effect of real interest rate on the Kuala Lumpur house prices, but it is not the case for the remaining five reported states in Peninsular Malaysia. The Granger-causality tests also provide positive findings. The direction of causation is from real interest rate to real MHPI (the Malaysian House Price Indexes). This study supports the ripple effect - the states' house prices are intercaused, except for Pulau Pinang. These findings are relevant for policy implications.